2018
DOI: 10.1007/s11065-018-9394-4
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Neglected’ Personal Neglect

Abstract: A review of patients with brain injury showing personal neglect is presented. The aim is to shed light on this aspect of neglect often unresearched or only indirectly investigated, and to discuss recent findings concerning the methods used to assess personal neglect, its neural correlates and its association with the more often explored aspect of extrapersonal neglect. The review was performed using PubMed and PsychInfo databases to search for papers published in the last 123 years (until January 2018). We rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 117 publications
(158 reference statements)
2
37
0
Order By: Relevance
“…The combined assessment of visual and personal neglect in our sample enabled us to evaluate the possibility of dissociated patterns of performance. Our results confirmed that MN can occur in the absence of signs of visual neglect [2], or of personal neglect [35]. The dissociation from personal neglect is of theoretical relevance, because it challenges the hypothesis that all MN patients simply do not pay attention to their contralesional limbs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The combined assessment of visual and personal neglect in our sample enabled us to evaluate the possibility of dissociated patterns of performance. Our results confirmed that MN can occur in the absence of signs of visual neglect [2], or of personal neglect [35]. The dissociation from personal neglect is of theoretical relevance, because it challenges the hypothesis that all MN patients simply do not pay attention to their contralesional limbs.…”
Section: Discussionsupporting
confidence: 77%
“…Actigraphy showed asymmetric motor behavior in all these patients, plus three more.The combined assessment of visual and personal neglect in our sample enabled us to evaluate the possibility of dissociated patterns of performance. Our results confirmed that MN can occur in the absence of signs of visual neglect[2], or of personal neglect[35]. The dissociation from personal neglect is of theoretical relevance, because it challenges the hypothesis that all MN patients simply do not pay attention to their contralesional limbs.In a subset of 25 right-brain damaged patients, we explored the lesional correlates of MN.Lesion location was heterogeneous, but frequently involved the white matter, including corticospinal tracts and long-range fronto-parietal and fronto-occipital fascicles.…”
supporting
confidence: 76%
“…To our knowledge, there are no investigations of potential lateralisation effects in the context of illusory full-body ownership perception. Future experimental studies should thoroughly examine this issue because we need to learn more about lateralisation in body ownership illusions and clarify how this relates to the literature on lateralisation of body representation [ 69 , 70 ], as well as neurological disorders of body representation [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Building a coherent representation of space entails a complex integration of different sensory inputs and output-related factors, in relation to different portions of space and coordinates systems. Coherently with this assumption, USN symptoms can dissociate across sensory modalities, 9 sectors of space (i.e., personal, peri-personal and extra-personal space [10][11][12][13][14], reference frames (egocentric vs allocentric neglect [15][16][17], and tasks. 18 An often neglected dissociation concerns symptoms affecting perceptual and output stages of spatial processing.…”
Section: Usn Is a Complex Syndromementioning
confidence: 99%